2021
DOI: 10.20867/tosee.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Soft Skills and Communication Skills in Tourism: Viewpoint From Tourists and Future Tourism Employees

Abstract: Purpose – Besides possessing professional knowledge, tourism service providers need to have expressed communication skills and soft skills in order to offer a better tourism service. In this paper, the tourism employees' set of soft and communication skills is analysed and compared from two different points of view: tourists on the one hand and future tourism professionals, i.e., tourism students, on the other. Therefore, the main purpose of this study is to analyse the importance and differences in the percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 68 publications
0
7
0
5
Order By: Relevance
“…Very limited research has examined how tourism frontline staff should be nurtured to become co-creators of memorable tourist experiences, particularly tourist guides. Studies conducted previously by authors such as El -Sharkawy (2007), Vasanthakumari (2019), Hine (2020), Demirović Bajrami et al (2020) andČuić Tanković, et al, (2021) identified a set of skills perceived to be more important than others at workplace and by tourist guides, including organisational skills, problem-solving skills, leadership, time management, customer care skills, health and safety skills, communication skills, knowledge of the destination and tourism products, right attitude concerning service, honesty and trustworthiness.…”
Section: Leadershipmentioning
confidence: 92%
See 4 more Smart Citations
“…Very limited research has examined how tourism frontline staff should be nurtured to become co-creators of memorable tourist experiences, particularly tourist guides. Studies conducted previously by authors such as El -Sharkawy (2007), Vasanthakumari (2019), Hine (2020), Demirović Bajrami et al (2020) andČuić Tanković, et al, (2021) identified a set of skills perceived to be more important than others at workplace and by tourist guides, including organisational skills, problem-solving skills, leadership, time management, customer care skills, health and safety skills, communication skills, knowledge of the destination and tourism products, right attitude concerning service, honesty and trustworthiness.…”
Section: Leadershipmentioning
confidence: 92%
“…The major soft skills perceived as the most important by business executives, also applicable to those in the tourism industry, include integrity, communication, courtesy, responsibility, social skills, positive attitude, professionalism, flexibility, teamwork, and work ethic (Robles, 2012). Robles (2012), Grančay (2020) andČuić Tanković et al (2021) indicates the required important personal attributes and skills of employees, including tourist guides, which are summarised in Table 1. Attributes such as being responsible, resourceful, and self -confident Robles (2012) states that even though all of the personal attributes and interpersonal qualities appear to be very important, not all are perceived to be equally important; some skills are more important when comparing them with other personal skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations